2010
DOI: 10.1089/gtmb.2009.0172
|View full text |Cite
|
Sign up to set email alerts
|

FMR1Protein Expression in Blood Smears for Fragile X Syndrome Diagnosis in a Mexican Population Sample

Abstract: Molecular diagnosis of fragile X syndrome (FXS) is carried out by Southern blot or polymerase chain reaction-Southern analysis; however, these procedures are expensive and time consuming, making it impractical for mass screening programs. Willemsen et al. developed and tested the diagnostic potential of a rapid antibody test on blood smears, based on the presence of fragile X mental retardation protein (FMRP) in peripheral lymphocytes from normal individuals and its absence in male patients with FXS. The diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this population, the authors reported very low levels of FMRP with an average percentage of stained lymphocytes of 8.6 per child, and no autistic behavior/FMRP interaction. The assay was also employed to study FMRP expression in a Mexican cohort comprising FXS patients and control individuals [56]. The authors reported that the sensitivity and specificity of the assay and the positive and negative predictive values were 100%.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In this population, the authors reported very low levels of FMRP with an average percentage of stained lymphocytes of 8.6 per child, and no autistic behavior/FMRP interaction. The assay was also employed to study FMRP expression in a Mexican cohort comprising FXS patients and control individuals [56]. The authors reported that the sensitivity and specificity of the assay and the positive and negative predictive values were 100%.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In recent years, antenatal diagnosis of FXS plays essential role in prevention of FXS (12)(13)(14). Study has found that single-tube polymerase chain reaction (PCR) panel of highly polymorphic markers is an efficient method for preimplantation genetic diagnosis of FXS (15).…”
Section: Introductionmentioning
confidence: 99%